Perbedaan Perilaku Kerja Dilihat dari Motivasi dan Stres Kerja Karyawan di Masa Pandemi COVID-19 - Delila Rambe; Ahmad Nurdin Hasibuan; Irma Setyawati (Jurnal Kajian Ilmiah, 2022)
This study aims to analyze differences in work behavior through work motivation and employee work stress during the pandemic and during the COVID-19 pandemic. This study uses a quantitative descriptive design by distributing questionnaires to employees in DKI Jakarta. The number of research samples is 100 people using snowball sampling technique. The problems in the study were tested by different tests with the paired sample t-test, MannWhitney (Wilcoxon), and Kruskall-Wallis. The results of this study are that the COVID-19 pandemic weakens work behaviors related to work stress even though work motivation does not. One of the causes of poor work behavior is because employees work from home. Currently, the main cause of increased work stress is because employees are facing increased unemployment since the spread of COVID-19; or female employees whose workloads are increasingly related to the dual roles of employees and teachers at home since school closures. On the other hand, there is no difference in work motivation before the outbreak of COVID-19, because employees have to earn daily income so they can support their families every day and avoid unemployment. As such, managers must comply with laws concerning employment regulations and disclose important information to employees. Managers need to evaluate layoff issues, evaluate and develop continuity plans according to government regulations to improve work and support employees and their families.